One, two, one pair! - McMillan, Bruce (New York : Scholastic Inc., 1991)
Photographs illustrate the concept of pairs through such examples as two hands, two skates, and two twins.
Booklist
1.1
K-3
Keywords: Two (The number) -- Juvenile literature; Number concept -- Juvenile literature; Counting -- Juvenile literature; Two (The number); Number concept; Counting; Two (The number); Number concept; Counting